China's public procurement protectionism and Europe's response: The case of medical technology - Fredrik Erixon; Anna Guildea; Oscar Guinea; Philipp Lamprecht (European Centre for International Political Economy (ECIPE), 2021)
This paper concerns China's market for medical technologies and how the Chinese state is assisting its own companies to gain greater sales at the expense of producers from Europe and other advanced manufacturing economies. The medical technology sector captures a variety of products, services and solutions which are essential to the provision of healthcare to citizens. Examples range from fairly simple technologies such as sticking platers, to complex ones, such as coronary stents, orthopaedics and pacemakers. In the last decades, Europe's exports of medical devices to China have grown robustly. On the back of vibrant innovation, firms from Europe and elsewhere have not just followed the growth of Chinese demand for medical devices - they have also increased their share of Chinese imports. Now, however, this market is at risk of being gradually closed off for European firms as China doubles down on various policies that advantage local firms, while ultimately harming innovation and Chinese patients.
Keywords: 330; Medizintechnik; Industriepolitik; Staatliche Einflussnahme; Öffentlicher Auftrag; Protektionismus; Importsubstitution; China; EU-Staaten